Neurological complications of CAR T cell therapy for cancers - Karschnia, Philipp; Dietrich, Jörg (Nature Reviews Neurology, 2025)
Genetically engineered chimeric antigen receptor (CAR) T cells have emerged as a powerful treatment option in patients with B cell malignancies, but neurological adverse effects are common and hamper the success of such therapies. Immune effector cell-associated neurotoxicity syndrome encompasses a wide range of acute neurological adverse effects, including encephalopathy with alterations in cognition and behaviour, language, motor function and coordination. In patients treated with CAR T cells for CNS malignancies, a more localized on-tumour, on-target neurotoxicity syndrome termed tumour inflammation-associated neurotoxicity can develop acutely, resulting in localized oedema with mass effect or in electrophysiological dysfunction with neurological symptoms. Following B cell maturation antigen-targeting CAR T cell therapies, delayed neurological complications, including cranial nerve palsies and a unique delayed-onset parkinsonism syndrome, are increasingly recognized. Management of neurological complications includes symptomatic treatments such as antiepileptic drugs or cerebrospinal fluid diversion, temporary immunosuppression with corticosteroids, various cytokine-targeting agents, and other distinct approaches depending on the nature of the toxicity. As our understanding of the mechanisms that contribute to the various neurological adverse effects of CAR T cell and other T cell-engaging therapies increases, novel treatment strategies to alleviate symptoms, as well as innovative CAR designs, promise to improve the safety and neurotoxicity of these powerful immunotherapies.
CRIS-Team Scopus Importer:2025-07-04